Place-aware content selection from dynamic web sources for public displays - Ribeiro, Fernando Reinaldo (2011)
“Copyright © [2009] IEEE. Reprinted from 5th International Conference on Signal-Image Technology & Internet-Based Systems. ISBN:978-1-4244-5740-3. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”